Highly regioselective C4-hydrazinylation of 2,4-dichloroquinolines: expedient synthesis of aminoquinoline substituted pyrrolidin-2,5-diones via hydrazinylquinolines - Kumar, Gopal Senthil; Zeller, Matthias; Gonnade, Rajesh Ghanshyam; Prasad, Kamam Jayarampillai Rajendra (Tetrahedron Letters, 2014)
A new class of hydrazinylquinoline regio-isomers has been synthesized through SNAr reaction of 2,4-dichloroquinolines with hydrazine hydrate. The reaction stops at the mono-substitution product with high regioselectivity at the C-4 rather than C-2 position of dichloroquinolines. The hydrazinylquinolines were subsequently converted into aminoquinoline substituted pyrrolidin-2,5-diones in the presence of Eaton's reagent. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 5-diones; Eaton's reagent; Hydrazinylquinolines; Pyrrolidin-2; Regioisomers; SNAr reaction